NOVEL “ORANG-ORANG PROYEK”: SEJARAH ORDE BARU - Ramis Rauf (TELAGA BAHASA, 2020)
This study wants to reveal the truth procedures in Ahmad Tohari's novel Orang-Orang Proyek, as a part of an event and a factor in the presence of a new subject. This research would answer the problem: how was the subjectification of Ahmad Tohari in Orang-Orang Proyek novel as truth procedures? This study used the set theory by Alain Badiou. The set theory explained that within a set there were members of "Existing" or Being and events as "Plural" members.  The results proved that the subjectivity between Tohari and New Order events produced literary works: Orang-Orang Proyek. This happened because there was a positive relationship between the author and the event as well as on the naming of the event. Not only as of the subject but also do a fidelity to what he believed to be a truth. The truth procedures or the void—originating from the New Order event—was in the history of the making of a bridge in a village in Java island, Indonesia during the New Order period that filled with corruption, collusion, and nepotism. Tohari then embodied it in his novel. By the presences of the novel, we could know the category of Tohari's presentation as a new subject such as faithful, reactive, and obscure.